EFL Lecturers’ Perspectives on Ethical Challenges in AI-Integrated English Language Teaching - Ariq Nafil Toris; Imam Santosa (Applied Research on English Education (AREE), 2026)
The use of AI in English as a foreign language (EFL) learning is one of the technology integration strategies to improve learning effectiveness, especially in higher education. However, many educators, especially lecturers, face ethical challenges in using AI technology into their teaching. This study observes the difficulties lecturers face in facing ethical challenges when integrating AI into their teaching, as well as bridging the gap between theoretical development and implementation in the classroom. Using a qualitative research design, data were collected through semi-structured interviews with four English lecturers who teach English as a foreign language in higher education and have various educational backgrounds. Then, the findings also observed that the ethical challenges lecturers face in using AI in learning are caused by misuse in the use of AI, the accuracy of AI in providing output, and the ambiguity of how the AI system stores user data. Thus, this challenge emphasizes that the effectiveness of AI technology depends on how well users understand how AI works. This study also explains the importance of a comprehensive considerate of AI for teachers and lecturers in higher education to improve the use of AI in EFL learning. Furthermore, these findings also explain the need for further research on how AI is used in EFL as a way to improve learning power that is relevant to current developments.Keywords: Use of AI; Learning effectiveness; Ethical challenges; EFL Classrooms